Experimental Mathematics. Volume 16, Number 1, 2007 - A K Peters (A K Peters, 2009)
Computing Decompositions of Modules over Finite-Dimensional Algebras Full TextPDF (187.9 KB) Authors Klaus M. Lux and Magdolna Szőoke 1-6